2009
DOI: 10.1111/j.1365-2222.2009.03273.x
|View full text |Cite
|
Sign up to set email alerts
|

Effector activity of peanut allergens: a critical role for Ara h 2, Ara h 6, and their variants

Abstract: Rationale-An important property of allergens is their ability to cross-link IgE and activate mast cells and basophils. The effector activity of peanut allergens has not been well characterized.Methods-Crude extracts of fresh peanut flour were fractionated by gel filtration. Effector function was assayed by measuring degranulation of RBL SX-38 cells sensitized with IgE from individual sera and from pools of sera of peanut allergic donors.Results-Following gel filtration, 75±7% of the applied protein and 76±16% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 52 publications
8
109
0
Order By: Relevance
“…A previous report found that Ara h 2 treated with trypsin/chymotrypsin displayed minimal reduction in IgE binding capacity, and mediator release from rat basophilic leukemia cells was not reduced by protease treatment, which was attributed to the proteolytic resistant core of Ara h 2 [23]. Additionally, studies have examined the effector activity of the peanut 2S albumins, Ara h 2 and 6, and have demonstrated that these proteins are the most potent peanut allergens in terms of degranulating basophils [7] and inducing anaphylaxis in a mouse model of peanut allergy [25]. Our current data show Ara h 2 fragments are present following any of the enzymatic hydrolyses, and thus may account for the persistent basophil reactivity we measured in response to the hydrolysates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous report found that Ara h 2 treated with trypsin/chymotrypsin displayed minimal reduction in IgE binding capacity, and mediator release from rat basophilic leukemia cells was not reduced by protease treatment, which was attributed to the proteolytic resistant core of Ara h 2 [23]. Additionally, studies have examined the effector activity of the peanut 2S albumins, Ara h 2 and 6, and have demonstrated that these proteins are the most potent peanut allergens in terms of degranulating basophils [7] and inducing anaphylaxis in a mouse model of peanut allergy [25]. Our current data show Ara h 2 fragments are present following any of the enzymatic hydrolyses, and thus may account for the persistent basophil reactivity we measured in response to the hydrolysates.…”
Section: Discussionmentioning
confidence: 99%
“…Ara h 3/4 has been recognized by serum IgE from 44 to 54% of patients with a history of peanut hypersensitivity [4,5]. Importantly, studies investigating the capacity of peanut proteins to cross-link IgE on effector cells have demonstrated that Ara h 2, together with its homolog Ara h 6, account for more than 80% of effector activity in peanut extracts [6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…Among the various immune mechanisms that are known to cause allergy, IgE mediated immune responses are responsible for most food allergy including severe and life threatening reactions to foods (Burks, 2002). All allergens are proteins but only a small number of proteins, for example the seed storage proteins 2S albumins (Ara h 2, Ara h 6), glycinin (Ara h 3) and beta-conglycinin (Ara h 1) and possibly four low-abundance proteins out of the hundreds of proteins present in peanuts are responsible for peanut food allergy (Porterfield et al, 2009;Peeters et al, 2007). The prevalence of food allergy is relatively low in the general population, ranging from 1 to 5% in adults to 6e8% in children (Thomas et al, 2005;Sicherer and Sampson, 2014).…”
Section: Food Allergy Risksmentioning
confidence: 99%
“…34) Despite water solubility of the seed albumins, a large amount of the peanut albumins could be extracted by NaCl buffer. 35) In a soybean 2D-GE model, little contamination of globulins and albumins was evident together with other hydrophilic proteins after one-step extraction by relatively high alcohol strength using 40% isopropanol.…”
Section: Discussionmentioning
confidence: 95%